EKOLOŠKO PRAVO IZMEĐU JAVNOG I PRIVATNOG PRAVA - Drenovak-Ivanović, Mirjana M. (Zbornik radova Pravnog fakulteta u Nišu, 2020)
Ugroženost prava ili interesa pojedinca prouzrokovano lošim stanjem ili povećanim zagađenjem životne sredine nikada ne ostaje povreda naneta samo tražiocu zaštite. Novi pravni instituti koji bi omogućili efikasniju, ekonomičniju, blagovremenu i suštinsku zaštitu prava na životnu sredinu određenog kvaliteta treba da urede pitanja od značaja za zaštitu kada je povređen ili ugrožen interes pojedinca ili grupe, ali i dalje od toga, kada je reč o povredi prava na zdravu životnu sredinu kao posebnog javnog interesa. Vezivanje zaštite tog prava za javni intres otvara pitanja značaja koje zaštita životne sredine ima u jednom društvu i načina na koji se vrši gradiranje javnih interesa među kojima je i interes zaštite životne sredine. U radu se, polazeći od navedene pretpostavke, ukazuje na načela ekološkog prava i dominantne karakteristike javnopravnog karaktera koje imaju uticaj na zaštitu prava na životnu sredinu određenog kvaliteta i u primeni privatnopravnih instituta pravne zaštite. Ključne reči: Interes zaštite životne sredine; - Javni interes; - Opštekorisna delatnost; - Zastupnici širih interesa javnosti; - Ekološka šteta. Environmental law between public and private law The basis for procedural protection of environmental rights is found in administrative procedure. To establishing guarantees of adequate and effective legal protection in environmental matters, general administrative procedure should be transformed. Traditionally one-party procedure, in environmental matters, the administrative procedure becomes, as a rule, two-party procedure, with the participation of public concerned. The legal framework for the protection of property rights that endangers or jeopardize the state of the environment is contained in the regulations of substantive law. Serbian legal system provides such protection by the general institutes in the field of compensation for damages and regulation of property rights. The case law provides many examples that point to numerous inconsistencies in the system of environmental protection in civil and administrative proceedings. Thus, for example, operators running activities which are of general-purpose are obliged to compensate injured persons only for damage exceeding normal limits. On several occasions, the case-law evidences that the compensation of non-material damage as a form of physical pain, due to the negative impact of industrial and adjacent objects on the environment, can only be granted if the existence of property damage exceeding the "normal limits" is established. In doing so, emissions must be of such intensity as to cause continuous physical pain. According to the case law, periodic emissions, even when they exceed the limit values during certain intervals, do not justify the compensation of non-material damage. The reasons for the underdeveloped legal institutes that provide environmental protection are found not only in the fact that the issues of protection of a healthy or adequate environment of certain quality belong to a branch of rights that has been developing since the 70s of the 20th century, but also in the fact that there is insufficient understanding of the principles on which environmental law is based and whose implementation means the necessary and essential change of legal instruments in public and private law. The plaintiffs in the procedure do not only protect their own rights and interests, but also the general interest of environmental protection. Infringement of the rights or interests of an individual caused by an increased environmental pollution would never remain a hindrance only to the protection seeker. New legal institutes that would allow more efficient, economical, timely and substantive protection of environmental rights should regulate issues of relevance to protection when an individual or group’s interest is endangered or jeopardized, but furthermore, in the event of a violation of environmental value as an object that should be protected as particular public interest. Linking the protection of this right to the public interest raises the issues of importance that environmental protection has in one society and the way in which the grading of public interests is done, among which is the interest of environmental protection. Starting from this assumption, the paper points to the principles of environmental law and the fact that environmental rights dominantly belong to public law that have an impact on the protection when legal institutes of private law are applied.